(untitled) (American Journal of Islam and Society, 2000)
The far-reaching implications of the debate surrounding sex education in state schools are summed up by the late Professor Syed Ali Ashraf in his Foreword to this book: "We are up against a tremendous conspiracy to dethrone the religious concept of a human being from the minds of people." Sex education is "just a modus operandi" of the "secularist philosophy" underpinning this conspiracy (p. 3). 1n presenting a number of essays on sex education from different faith and nonfaith perspectives, the editors have succeeded in introducing readers not only to Islamic concepts of sexual relationships and sex education, but also to the ideological battle that is being played out with children’s education. At the very heart of this debate we find unanswered and unanswerable questions about liberal democracy and how liberal it can be in allowing minorities to flourish in its midst. The argument basically revolves around the liberal push for increasing individual rights and to see how far such rights can go in relation to responsibilities. As Carole Ulanowsky notes in her contribution titled "Sex Education: Beyond Information to Values," the balance has tipped in favor of rights - a position that is (perhaps) suitable for the mature educator but which "can leave young people morally adrift" (p. 22). In his overview titled "Values and Sex Education in a Multicultural Society," Mark Halstead demonstrates that this issue is complex and laced with difficulties; however, "the promotion of ’responsible sexual behavior’ has become a dominant motif in contemporary sex education in Britain as in other western countries" (p. 236). But who is to decide what is "reasonable"? Parents? Educators? Or that thorn in the side of liberal sex educators: religion? In stating Islamic positions on this subject, Noibi and Abdul Mabud cover ground that has been well-presented elsewhere; however, the fact that their contributions are neither out of place nor dated illustrates how little educators have learnt from earlier publications by Muslims on this subject. An alternative, less charitable view might conclude that the liberal sex education lobby has learnt too much about the Islamic position and has, as a result, strengthened efforts to undermine it. For example, Michael Reiss proposes that "the way forward may be for society to make it easier for homosexuals to live in lasting and mutually faithful sexual relationships" (p. 146), and David Carr asks, "How could any civilized person see it as other than a moral advance over bygone tyrannies that homosexual men and women are no longer persecuted?" (p. 170). Going further, Carr says that "liberal modernity has at least freed us from a range of irrational prohibitions." This stand taken by both men demonstrates how "liberal values" can in fact be imposed on young people and, in doing so, force them to alter their own beliefs (and possibly practices). Carr’s implication is that the prohibition of homosexuality in scriptures is "irrational," thereby making his own statement "rational." But on what grounds can he make such a judgment? As a number of contributions remind us, education is not value-free, and it is a myth to suggest that the liberal view of sex education is either neutral or morally superior to other views. Abdul Mabud puts it succinctly: "Passivity [and] neutrality" in sex education are themselves "values" (p. 110) ...